Research and application of intersection traffic signal control algorithm based on vehicle location. (28th February 2020) - Wang, Zhichao; Li, Min; Tang, Liang; Huang, Jun Steed
This paper focuses on the optimising algorithms of signal timing of urban intersection combined with vehicle location using the platform of the new type of wireless electronic license plate system. With the traffic flow information obtained from the platform, a dynamic optimisation model with optimal control parameters of green light time of all four phases for single intersection is constructed. Then genetic algorithm is applied to obtain the satisfying signal timing scheme. In simulation examples, the proposed dynamic distribution method and the traditional time control method are compared. The results show that compared with the traditional time control method, in traffic rush hour, the genetic optimisation algorithm can reduce the waiting time by 23% with the same road vehicle capacity. At non-peak time, the proposed method can reduce the waiting time by 10%. Therefore, the introduced method can effectively reduce the total queue delay, and improve the traffic capacity of the intersection.